Professional identity and shared decision making among psychiatry residents: designing a brief teaching module. Issue 2 (12th March 2018) - Bentley, Kia J.; Cummings, Cory R.; Casey, Rachel C.; Kogut, Christopher P.
Abstract : Purpose: The purpose of this paper is to increase awareness of shared decision making, the initial aim of the study was to understand how psychiatrists-in-training defined themselves as unique among physicians with an eye on how professional identity might shape approach to care. The second aim was to use those definitions and descriptions related to professional identity and tailor a brief training module to promote awareness of the shared decision making model. Design/methodology/approach: The authors do this by first conducting focus groups to ascertain how psychiatric residents characterize their professional identity and unique disciplinary characteristics. The authors then designed a brief training session that exploits the relationship between how they define themselves as physicians and how they approach clinical decision making with patients. Findings: Three major themes that emerged from the focus group data: the central role of societal and treatment contexts in shaping their professional identity and approaches to care, a professional identity characterized by a great sense of pride, and a strong commitment to systematic decision-making processes in practice. While the assessment of the training module is preliminary and lacks rigor for any generalizability or statements of causality, responses likely affirm the training tailored around professional identity as a possible vehicle for effective exposure to the concept of shared decision making and served as a useful avenue for self-reflection about needed changes to more fully embrace the practice. Research limitations/implications: More inquiry may be needed into the association between trust, relationship longevity and power and paternalism, as a way to bring greater insight into the adoption of shared decision making. Future research will have to investigate whether or not including identity-related content is empirically connected to successful training on shared decision making. Likewise, future research should also look at the reciprocal impact of effectively using shared decision making on the affirmation of professional identity among psychiatrists, and indeed all who embrace patient-centered care. Originality/value: This is the one of the first papers to investigate issues of professional identity among psychiatry residents, and also among the first papers to consider the relationship between professional identity and use of shared decision making.